The Impact of Humble Leadership on Workplace Wellbeing: The Role of Pride as a Mediator and Proactive Personality as a Moderator (Journal of Asian Development Studies, 2023)
The positive effects of humble leadership on employees have been examined through numerous studies. Conversely, its influence on the well-being of newcomers has been explored infrequently. Based on positive emotions theory, i.e., broaden and build theory and affective event theory, the current paper anticipated mediation moderated mechanism to discover the impact of humble leaders on the well-being of newcomers. It identified the pride of the newcomer as mediation and the newcomer’s proactive personality as moderation. Data was collected in two waves through a self-administered questionnaire from 316 newcomers working in the educational sector. The theorized model was checked via confirmatory factor analysis. Humble leadership was positively related to newcomers’ well-being, and the pride of newcomers mediated this association. Moreover, the proactive personality of the newcomer moderated the relationship between humble leadership and the newcomer’s pride. Although it is advantaged from two-wave data, a significant limitation of this research is its cross-sectional data nature, making it hard to draw cause-effect relationships. Moreover, data collected from newcomers’ self-reports may raise standard method variance. This study attempts to inspect the humble leadership role in advancing the pride and well-being of newcomers.